2015
DOI: 10.1017/s2040174415007850
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of steroid-resistant nephrotic syndrome: relationship between polymorphism -173 G to C in the MIF gene and serum level MIF in children

Abstract: There is no satisfactory explanation as to why some nephrotic syndrome (NS) patients respond to glucocorticoids and others do not. The aim of this study was to investigate an association between single nucleotide polymorphism of the MIF gene -rs755622 and serum MIF concentrations in NS patients. During a period between November 2011 and September 2012, 120 consecutive children divided into three groups [healthy children, steroid-resistant nephrotic syndrome (SRNS) and steroid-sensitive nephrotic syndrome (SSNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…We included this model in the analysis to determine if a strong influence of a single allele on disease was present, however, this was not the case. The localization of the polymorphism on the promoter sequence indicates that its biological significance is related to differences in the transcript expression levels (Matia-García et al, 2015 ; Ramayani et al, 2016 ; Bae and Lee, 2017 ), and this differences are better explained in an individual by genotypes than by alleles. The use of the allelic model duplicates the data available for analysis in comparison to genotypes, but does not provide useful information on the relation with disease, considering the nature of the polymorphism, and indicating that this model is not useful in our current analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included this model in the analysis to determine if a strong influence of a single allele on disease was present, however, this was not the case. The localization of the polymorphism on the promoter sequence indicates that its biological significance is related to differences in the transcript expression levels (Matia-García et al, 2015 ; Ramayani et al, 2016 ; Bae and Lee, 2017 ), and this differences are better explained in an individual by genotypes than by alleles. The use of the allelic model duplicates the data available for analysis in comparison to genotypes, but does not provide useful information on the relation with disease, considering the nature of the polymorphism, and indicating that this model is not useful in our current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism has been associated with the pathophysiology of arthritis, infections and inflammatory-related diseases (Donn et al, 2001 ; Baugh et al, 2002 ). The importance of this variant is due to its localization on the CpG island of the MIF promoter, where the G > C change generates an additional CpG motif and binding site for the transcription factor activator protein 4 (AP4) (Donn et al, 2001 ), which in turn increases the levels of both transcripts and protein (Matia-García et al, 2015 ; Ramayani et al, 2016 ; Bae and Lee, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The allele MIF-173*C (rs755622) is associated with higher serum MIF levels. Several studies have been conducted to investigate the potential role of this genetic polymorphism in the gene encoding for MIF in patients with nephrotic syndrome [ 71 , 79 81 , 104 , 105 ]. A meta-analysis conducted by Tong et al showed that the gene polymorphism rs755622 plays an important role in the risk of glucocorticoid resistance in patients with nephrotic syndrome [ 106 ].…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…One study did not explicitly classify INS into SSNS and SRNS according to steroid responsiveness (13), so we excluded it in the meta-analysis of MIF -173 G>C polymorphism and steroid responsiveness. In the other six studies, three studies provided a specific definition of steroid resistance (14)(15)(16). According to the NOS scale, all the included studies were considered to be of high quality (score ≥ 6).…”
Section: Study Characteristicsmentioning
confidence: 99%